14-2q-5=-2q+9

Simple and best practice solution for 14-2q-5=-2q+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-2q-5=-2q+9 equation:


Simplifying
14 + -2q + -5 = -2q + 9

Reorder the terms:
14 + -5 + -2q = -2q + 9

Combine like terms: 14 + -5 = 9
9 + -2q = -2q + 9

Reorder the terms:
9 + -2q = 9 + -2q

Add '-9' to each side of the equation.
9 + -9 + -2q = 9 + -9 + -2q

Combine like terms: 9 + -9 = 0
0 + -2q = 9 + -9 + -2q
-2q = 9 + -9 + -2q

Combine like terms: 9 + -9 = 0
-2q = 0 + -2q
-2q = -2q

Add '2q' to each side of the equation.
-2q + 2q = -2q + 2q

Combine like terms: -2q + 2q = 0
0 = -2q + 2q

Combine like terms: -2q + 2q = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -8v-4v= | | -3*-5=51 | | 8g-2g= | | p=45-q | | 9q+(-4q)= | | 92=4+6w+2w | | 7w+4w= | | 8p+(-6p)+6m= | | 6r+5t+4r= | | 8e+3(5+e)=10 | | 6x+8(2x+3)= | | 2x+3+3x+2=180 | | 5(x-6)+8=7x-10 | | 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= | | 7x+-12=2 | | 30x-25=50-20x | | -8d-(-2d)-6d= | | 16-x+2=23 | | 15b-24b= | | 888x=111 | | 7t+4t= | | N=zx-d | | 6rs+5r+8s-rs-r-s= | | 6-5j=-94 |

Equations solver categories